EVALUATION OF TREATMENT EFFICIENCY FOR MULTIPLE DRUG RESISTANT TUBERCULOSIS PATIENTS IN SIBERIAN AND FAR EASTERN FEDERAL DISTRICTS - O. P. Filippova; O. V. Revyakina; T. V. Alekseeva (Туберкулез и болезни лёгких, 2015)
The rate of spread of multiple drug resistant strains is much higher in Siberian and Far Eastern Federal Districts compared to the rest of Russia. In the meantime due to the lack of the unified monitoring system for this group of patients it is impossible to evaluate treatment outcomes.Basing on the data submitted by 21 regions of Siberia and Far East the treatment e`ciency has been analyzed for patients suwering from multiple drug resistance for all these regions in general and specifically for each region, and the main factors providing the impact on the outcome have been identified.Half of the registered patients do not receive adequate treatment with second line drugs for various reasons. Treatment e`ciency for the patients enrolled into treatment is almost the same as in the cohorts in the regions where the projects approved by Green Light Committee (WHO) were implemented.